136k views
3 votes
(5x² - 8x + 1) + (2x2 - 4x - 11)

1 Answer

0 votes

Answer:

7x^2 −12x−10

Explanation:

((5x2 - 8x) + 1) + (2x2 - 4x - 11)

Factoring 7x2-12x-10

The first term is, 7x2 its coefficient is 7 .

The middle term is, -12x its coefficient is -12 .

The last term, "the constant", is -10

Step-1 : Multiply the coefficient of the first term by the constant 7 • -10 = -70

Step-2 : Find two factors of -70 whose sum equals the coefficient of the middle term, which is -12 .

-70 + 1 = -69

-35 + 2 = -33

-14 + 5 = -9

-10 + 7 = -3

-7 + 10 = 3

-5 + 14 = 9

-2 + 35 = 33

-1 + 70 = 69

Observation : No two such factors can be found !!

Conclusion : Trinomial can not be factored

User CJBS
by
4.0k points